KSU aerobic swine waste handling system - a progress report - Koch, B.A.; Allee, G.L.; Lipper, R.I.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
At the KSU swine research unit, the aerobic oxidation waste-disposal system continues to function satisfactorily. Though problems and maintenance are minimal, routine observation and maintenance are necessary to prevent development of problems. Odor is not a problem. Waste fluid can be spread on fields any time that soil is not too wet and--regardless of wind direction or humidity conditions--nearby neighbors do not complain. Pigs are performing satisfactorily in all buildings. Flies are easily controlled, suitable sanitation is easily maintained, and working conditions are satisfactory.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; KSU aerobic swine waste handling system; Aerobic oxidation